PIC: Practical Internet Coordinates for Distance Estimation - Costa, Manuel; Castro, Miguel; Rowstron, Ant; Key, Peter (2004)
This paper introduces PIC, a practical coordinate-based mechanism to estimate Internet network distance (i.e., round-trip delay or network hops). Network distance estimation is important in many applications, for example, network-aware overlay construction and server selection. There are several proposals for distance estimation in the Internet but they all suffer from problems that limit their benefit. Most rely on a small set of infrastructure nodes that are a single point of failure and limit scalability. Others use sets of peers to compute coordinates but these coordinates can be arbitrarily wrong if one of these peers is malicious. While it may be reasonable to secure a small set of infrastructure nodes, it is unreasonable to secure all peers. PIC addresses these problems: it does not rely on infrastructure nodes and it can compute accurate coordinates even when some peers are malicious.We present PIC’s design, experimental evaluation, and an application to network-aware overlay construction. Our results indicate that PIC can reduce the overhead of network-aware overlay construction by almost an order of magnitude.
ICDCS